Obstructive uropathy associated with a Retzius space hematoma following postpartum pulmonary embolism - Soo Youn Song; Dan Bit Park; Mina Lee; Hyun Jeong Song; Mia Park; You Jin Kim; Byung Hun Kang; Young Bok Ko; Heon Jong Yoo (IMR Press, 2022)
Background: To report on a case of acute renal failure associated with a Retzius space hematoma that had been extended to retroperitoneal space, following pulmonary embolism treatment in the postpartum period. Case report: A 30-year-old woman was transferred to the hospital for syncope on the first postoperative day following cesarean section. There were no active vaginal bleeding or intra-abdominal bleeding. On diagnosis of pulmonary embolism, she was treated with extracorporeal membrane oxygenation with heparinization. On day 4, ultrasonography showed newly developed hematoma at the anterior side of the uterus, and transarterial embolization was performed. On day 5, she developed acute kidney injury but there were no increase in size of the hematoma on ultrasonography. She recovered after 3 days of renal replacement therapy. However, on day 10, she showed tachycardia and increased serum creatinine. Computed tomography revealed not only a 15-cm hematoma anterior to the uterus, but also another 17-cm hematoma in the retroperitoneal space under the left kidney. Exploratory laparotomy was performed for obstructive uropathy and hematomas were evacuated. The patient's vital sign stabilized one day following surgery. Conclusion: When treating postpartum patients with pulmonary embolism, physicians should be aware of the possibility of a concealed hemorrhage in the Retzius space and of subsequent kidney injury.